2014
DOI: 10.3748/wjg.v20.i36.12847
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis ofHelicobacter pylori: What should be the gold standard?

Abstract: Since the discovery of Helicobacter pylori (H. pylori) in 1983, numerous detection methods for the presence of the bacterium have been developed. Each one of them has been associated with advantages and disadvantages. Noninvasive tests such as serology, (13)C urea breath test (UBT) and stool antigen tests are usually preferred by the clinicians. Serology has its own limitation especially in endemic areas while (13)C UBT is technically very demanding. The stool antigen detection method, although specific, is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
295
2
23

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(325 citation statements)
references
References 158 publications
5
295
2
23
Order By: Relevance
“…Although PCR could be performed even with a traces of bacterial DNA, it is mainly considered as an invasive method that needs biopsy. 16 On the other hand simple breath tests (UBT), serology and stool antigen test as well as Enzyme-Linked Immunosorbent Assay (ELISA) are known as noninvasive assays which are usually used for patients who are not advised undergoing gastroscopy. 17 To date, several commercially available ELISA kits have been used for detection of H. pylori infection which differs in target antigens and antibody preparations.…”
mentioning
confidence: 99%
“…Although PCR could be performed even with a traces of bacterial DNA, it is mainly considered as an invasive method that needs biopsy. 16 On the other hand simple breath tests (UBT), serology and stool antigen test as well as Enzyme-Linked Immunosorbent Assay (ELISA) are known as noninvasive assays which are usually used for patients who are not advised undergoing gastroscopy. 17 To date, several commercially available ELISA kits have been used for detection of H. pylori infection which differs in target antigens and antibody preparations.…”
mentioning
confidence: 99%
“…Confirming H. pylori status in people with diagnosed GML is a routine procedure [39]. It is suggested that besides detecting such bacteria, an important diagnostic element may also be in determining the H. pylori virulence profile.…”
Section: Implications For Medical Practice and Teachingmentioning
confidence: 99%
“…For this reason, H. pylori infection should be confirmed in each patient diagnosed with GML. The diagnosis should be based on invasive and noninvasive tests including measuring IgG, IgM, IgA antibodies, monoclonal stool antigens detection, the 13 C-urea breath test, microbes culture and histochemical testing [39]. H. pylori eradication therapy should rely on highly effective antibiotics with due consideration given to possible resistance in bacterial strains [5].…”
Section: Gastric Malt Lymphoma Treatmentmentioning
confidence: 99%
“…However, while PCR tests for antibiotic resistance and pathogenicity are well established and commercialised in Europe and Asia, the large numbers of apparent 'false positives' (positive PCR in histologically normal biopsies) has limited its clinical applications as markers of infection. 6 …”
mentioning
confidence: 99%
“…3 Acid reflux in BO is often silent. 4,5 The G-protein b3 subunit gene has been implicated in signal transduction of neurotransmitters 6 …”
mentioning
confidence: 99%